PENGARUH MODEL TALKING STICK TERHADAP HASIL BELAJAR IPS SISWA KELAS III - Nursaadah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract The influence of the talking stick model on the learning outcomes of IPS students class III. This study aims to find out how big the influence of the talking stick model on the results of IPS learning. The method used in this research is experimental method, with nonequivalen control group design. Collecting technique is measurement technique. Based on result of data analysis, the mean of learning result of student of control class equal to 66,28 while experiment class equal to 81. The result of hypothesis test (t-test) using t-test pollad variance was obtained tcount of 6.82 and ttable 2.021 (significance level (Î±) = 5% and dk = 48) showed that tcount is greater than ttable then Ha is accepted. From the calculation of Effect size, obtained 0.90 (high criteria) This means talking stick model gives a high influence on the learning outcomes of third grade students of Elementary School 03 Pontianak City. Keywords: Influence, Model Talking Stick, Learning Outcomes